2003
DOI: 10.1096/fj.02-0576fje
|View full text |Cite
|
Sign up to set email alerts
|

Role of the MET/HGF receptor in proliferation and invasive behavior of osteosarcoma

Abstract: Signal transduction downstream HGF receptor (MET) activation involves multiple pathways that account for mitogenesis, motility and morphogenesis in a cell type-dependent fashion. MET receptor is aberrantly expressed in almost 100% of human osteosarcomas. We analyzed the effect of the MET receptor activation in five human osteosarcoma cell lines evaluating the levels of HGF-dependent activation of MAPK and PKB/AKT as biochemical readouts of mitogenic and invasive responses, respectively. All the cell lines test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
74
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 73 publications
(77 citation statements)
references
References 48 publications
(39 reference statements)
2
74
1
Order By: Relevance
“…(57) It is likely that several metastatic processes are linked to c-MET signaling, including cell motility, invasion, proliferation, and survival. (58) Since c-MET is a growth factor receptor with an intracellular tyrosine kinase activity, the development of small-molecule inhibitors of c-MET has been possible. The inhibition of c-MET has been effective in suppressing metastatic phenotype in osteosarcoma cells and preclinical models.…”
Section: Etiology Of Osteosarcomamentioning
confidence: 99%
“…(57) It is likely that several metastatic processes are linked to c-MET signaling, including cell motility, invasion, proliferation, and survival. (58) Since c-MET is a growth factor receptor with an intracellular tyrosine kinase activity, the development of small-molecule inhibitors of c-MET has been possible. The inhibition of c-MET has been effective in suppressing metastatic phenotype in osteosarcoma cells and preclinical models.…”
Section: Etiology Of Osteosarcomamentioning
confidence: 99%
“…7 MET activity was associated with proliferation, metastasis and chemotherapy resistance in osteosarcomas, and K252a, a specific MET-inhibitor, was able to revert HGF dependent growth of osteosarcoma cells in vitro, emphasizing its oncogenic role. [8][9][10] The role of MET in ES is however largely unknown.…”
mentioning
confidence: 99%
“…Overall, in vitro results with PF-2341066 were consistent with published reports using other Met inhibitors (eg, SU11274 and PHA-665752) to inhibit the malignant behavior of cultured OS cells. (3,21,22) Until recently, the OS field lacked a clinically relevant xenograft model capable of recapitulating the features of human OS, including mixed osteoblastic/lytic lesions in the metaphyseal region of the humerus, femur, or tibia and pulmonary metastasis. (1,2) MNNG cells are one of several recently characterized OS cell lines that mimic human OS when orthotopically xenografted into nude mice.…”
Section: Discussionmentioning
confidence: 99%
“…(20) Despite the important role of Met in the development and maintenance of OS, pharmacologic Met inhibition has been addressed only in in vitro studies. (21,22) These studies demonstrated that Met inhibitors antagonize liganddependent and -independent OS proliferation, survival, and motility. (21,22) Given the importance of Met signaling in human OS, we hypothesized that the novel, orally bioavailable Met inhibitor PF-2341066 (15,23) would have efficacy in an orthotopic xenograft model of OS.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation